Faktor Pendukung dan Kontribusi Kecamatan bagi Kecukupan Konsumsi Beras di Kabupaten Jombang, Jawa Timur - nFN Sumarsono; nFN Minto; Sulung Rachmawan Wira Ghani; Totok Yulianto (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2020)
Vulnerability of food insecurity is closely related to food sufficiency, especially rice as a staple food. The purpose of this risearch was to analyze supporting factors and to identify sub-districts contribution to the rice consumption adequacy in Jombang Regency, East Java. Data used in this study was a panel data of cross-sectional from 21 sub-districts and time series data of the period 2010 to 2016. A regression analyses and a biplot analyses were used in this study. Research results showed that three ot of five factors were linear positive in supporting the adequacy of food consumption, namely rice procurement, productivity of rice farming, and rice harvested acreage; rice consumption was linear negative, and rice prices was not significant. The variability of rice consumption was identified as the highest among the supporting factors, similarity in supporting factor characteristics was exist in eight sub-district groups, and the superiority of factor scores was identified in three sub-districts groups. The policy implication from this study, among others, are a program for the rice consumption adequacy should be designed based on eight sub-districts groups with the similarity characteristics in orders to achieve efficiency ini costs, time, and manpower; and a supply chain among sub-districts should be developed by prioritizing the rice flow from the above average consumption adequacy rate of sub-districts groups to the below average one.